Kepastian Hukum atas Akta Risalah Lelang yang Dibuat Oleh Notaris Selaku Pejabat Lelang Kelas II yang Cacat Hukum Prosedural - Sulkifli Sulkifli; Yudha Cahya Kumala; Permata Nauli Daulay (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study examines the issue of procedural legal defects in auction minutes deeds prepared by notaries acting as Class II Auction Officials, which often lead to legal uncertainty and potential losses for the parties involved. The objective of this research is to analyze preventive measures against such procedural defects and to assess the extent of legal certainty of the resulting deeds. This research employs a normative juridical method based on secondary data, utilizing statutory, case, conceptual, and analytical approaches. The study is grounded in Jan Michiel Otto’s theory of legal certainty and Paul Klemperer’s auction theory. The findings indicate that preventing procedural defects requires a comprehensive four-layer model consisting of regulatory harmonization, professional capacity building of notaries, the implementation of technology-based auction systems, and consistent supervisory mechanisms. Furthermore, the level of legal certainty of auction minutes deeds depends on the severity of the procedural defects, which can be classified into three categories: severe defects rendering the deed null and void, moderate defects making it voidable, and minor defects that do not affect its validity. Regulatory inconsistencies and weak supervision are identified as the main factors contributing to legal uncertainty.